EDUKASI PENCEGAHAN DAN PENYALAHGUNAAN NAPZA DI POSYANDU REMAJA ANGGUN NAN TONGGA KELURAHAN KAMPUNG JAWA I KOTA PARIAMAN - Trisfa Augia; Mery Ramadani; Yessy Markolinda; Ranny Firsti; Hanifah S (BULETIN ILMIAH NAGARI MEMBANGUN, 2022)
According to WHO, adolescents are a group of population in the age range of 10-19 years; however, the Indonesian Ministry of Health stated adolescents are a group of people in the age range of 10-18 years. Adolescents as an active age group and have a high curiosity are groups that looking for self-identity, trying new things so that they are easily influenced by peers and other people in the community. This group needs directed guidance and support from the family and community to prevent bad influences and inappropriate attitudes and behaviors. One of the problems in adolescents is drug abuse. The purpose of this community empowerment was to prevent drugs abuse amongst teenagers by educating and delivering appropriate information through Adolescent Integrated Service Post (Posyandu). A team of lecturers from the Faculty of Public Health, Andalas University conducted an interactive training on August 19, 2021, presenting 20 teenagers and cadres at an adolescent Integrated Service Post newly formed, Anggun Nan Tongga in Kampung Jawa I Village, Pariaman. It was initiated by the community. The program was followed by coaching and evaluation of activities. In conclusion, this forum requires support from government agencies and educational institutions such as the Central Pariaman Sub-District, the Head of Village, and the Pariaman Health Center. Posyandu is one of the forums to deliver health services closer to adolescents and preventive and promotive efforts in the health sector. The teenagers appreciated the community service activity, and hopefully this community empowerment can be performed continuously.